UBTF tandem duplications in pediatric myelodysplastic syndrome and acute myeloid leukemia: implications for clinical screening and diagnosis - Barajas, Juan M.; Umeda, Masayuki; Contreras, Lisett; Khanlari, Mahsa; Westover, Tamara; Walsh, Michael P.; Xiong, Emily; Yang, Chenchen; Otero, Brittney; Arribas-Layton, Marc; Abdelhamed, Sherif; Song, Guangchun; et al. (Haematologica (Roma), 2024)
Recent genomic studies in adult and pediatric acute myeloid leukemia (AML) demonstrated recurrent in-frame tandem duplications (TD) in exon 13 of upstream binding transcription factor (UBTF). These alterations, which account for ~4.3% of AMLs in childhood and about 3% in adult AMLs under 60, are subtype-defining and associated with poor outcomes. Here, we provide a comprehensive investigation into the clinicopathological features of UBTF-TD myeloid neoplasms in childhood, including 89 unique pediatric AML and 6 myelodysplastic syndrome (MDS) cases harboring a tandem duplication in exon 13 of UBTF. We demonstrate that UBTF-TD myeloid tumors are associated with dysplastic features, low bone marrow blast infiltration, and low white blood cell count. Furthermore, using bulk and single-cell analyses, we confirm that UBTF-TD is an early and clonal event associated with a distinct transcriptional profile, whereas the acquisition of FLT3 or WT1 mutations is associated with more stem celllike programs. Lastly, we report rare duplications within exon 9 of UBTF that phenocopy exon 13 duplications, expanding the spectrum of UBTF alterations in pediatric myeloid tumors. Collectively, we comprehensively characterize pediatric AML and MDS with UBTF-TD and highlight key clinical and pathologic features that distinguish this new entity from other molecular subtypes of AML.